2021
DOI: 10.1038/s41467-021-22656-5
|View full text |Cite
|
Sign up to set email alerts
|

Extreme melt season ice layers reduce firn permeability across Greenland

Abstract: Surface meltwater runoff dominates present-day mass loss from the Greenland Ice Sheet. In Greenland’s interior, porous firn can limit runoff by retaining meltwater unless perched low-permeability horizons, such as ice slabs, develop and restrict percolation. Recent observations suggest that such horizons might develop rapidly during extreme melt seasons. Here we present radar sounding evidence that an extensive near surface melt layer formed following the extreme melt season in 2012. This layer was still prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 71 publications
7
48
0
Order By: Relevance
“…Although the AR-derived spatially coherent melt layer detections are often observed to be adjacent to perennial firn aquifer and ice slab areas, these sub-facies were masked in the original airborne ice-penetrating radar survey analysis by Culberg et al (2021). Spatially coherent melt layers often overlay perennial firn aquifers (e.g., Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the AR-derived spatially coherent melt layer detections are often observed to be adjacent to perennial firn aquifer and ice slab areas, these sub-facies were masked in the original airborne ice-penetrating radar survey analysis by Culberg et al (2021). Spatially coherent melt layers often overlay perennial firn aquifers (e.g., Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal meltwater was refrozen into spatially coherent melt layers following the 2010 and 2012 melting seasons (Culberg et al, 2021) as well as more recently following the 2015 and 2018 melting seasons identified as part of the temporal L-band signature analysis in this study (Sect. 2.3.1).…”
Section: Can Influencementioning
confidence: 99%
See 2 more Smart Citations
“…Chemistry, physics, and material science on laser devices, ion energy, and photoelectrochemical power [9]- [11]. Environmental and earth science on climate and ocean dynamics [12]- [14]. Automotive and transportation engineering including self-driving techniques [15]- [17].…”
Section: A Background Of Variable Dependence Detectionmentioning
confidence: 99%